2022
DOI: 10.1016/j.pmedr.2021.101685
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-vigorous intensity physical activity among adolescents in the USA during the COVID-19 pandemic

Abstract: This study aimed to evaluate adolescents’ moderate-to-vigorous intensity physical activity (MVPA) during the COVID-19 pandemic by sociodemographic characteristics, and to determine mental health and resiliency factors associated with MVPA among a diverse national sample of adolescents ages 10-14 years. Data were collected during the pandemic in May 2020 from the Adolescent Brain Cognitive Development Study (ABCD, N=5,153), a national prospective cohort study in the U.S. MVPA was quantified as the product of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 41 publications
(54 reference statements)
2
36
0
3
Order By: Relevance
“…The percentage of the adolescents meeting Health and Human Services’ (HHS) moderate-to-vigorous physical activity (MVPA) guidelines, defined as 60 minutes of moderate to strenuous physical activity, decreased from 16.1% (pre-pandemic) to 8.9% (during the pandemic- May 2020). 2 , 3 Given that excessive screen time and low physical activity are associated with poor adolescent physical health outcomes such as obesity and negative mental health outcomes such as higher rates of depression and anxiety, understanding correlates for elevated sedentary behaviors is critical to designing effective screenings and interventions. 1 , 3 , 4 , 5 , 6 In addition, given that the biggest rise in obesity prevalence is seen in late childhood to early adolescence, it is vital to examine screen time and physical activity potential risk factors in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of the adolescents meeting Health and Human Services’ (HHS) moderate-to-vigorous physical activity (MVPA) guidelines, defined as 60 minutes of moderate to strenuous physical activity, decreased from 16.1% (pre-pandemic) to 8.9% (during the pandemic- May 2020). 2 , 3 Given that excessive screen time and low physical activity are associated with poor adolescent physical health outcomes such as obesity and negative mental health outcomes such as higher rates of depression and anxiety, understanding correlates for elevated sedentary behaviors is critical to designing effective screenings and interventions. 1 , 3 , 4 , 5 , 6 In addition, given that the biggest rise in obesity prevalence is seen in late childhood to early adolescence, it is vital to examine screen time and physical activity potential risk factors in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings have implications for clinical and research practices in regards to measuring adolescent physical activity. Given decreases in MVPA during the pandemic [51] and discrepancies in parent-adolescent reporting of MVPA, parents could discuss and encourage MVPA with their adolescents. Pediatricians could consider assessing for and promoting MVPA for adolescents and their parents at primary care visits during the pandemic.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…65 A large national sample of adolescents in the United States surveyed early in the COVID-19 pandemic found that a lower proportion of racial/ethnic minority adolescents and those from lower socioeconomic status households met moderateto-vigorous physical activity guidelines during the pandemic compared to those from higher socioeconomic status households. 66…”
Section: Young Adultsmentioning
confidence: 99%